PENINGKATAN KOMUNIKASI MATEMATIS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TSTS SISWA KELAS VIII SMP - Astri Yuniartati; Sumargiyani Sumargiyani (Universitas Muhammadiyah Semarang, 2018)
This research was carried out based on the existing conditions, the students were less communicative with the teacher and student’sawareness of the importance of the discussion was still low. This studyaims to improve student communication with cooperative learning modeltype Two Stay Two Stray In class VIII B Junior High School 4 Sewoneven semester academic year 2017/2018. This research is an actionresearch. The study was conducted in two circles, one cycle consisting oftwo meetings. The research subjects were students of grade VIII B Junior High School 4 Sewon Bantul Yogyakarta, totaling 32 students. The object of this research is mathematical communication of students inmathematics learning with cooperative learning model type two stay twostray. Data collection techniques berupa observation and interviews. Theinstruments used are a student mathematical communication observation, teacher observation, and interview. Data analysis usesqualitative descriptions. The indicators of success are shown byincreasing mathematical communication that achieves good criteria. Theresults showed that the percentage of students mathematicalcommunication skill in cycle I was 38.35% with less criteria. The cycle IIit increased to 62.84% with good criteria. Keywords: communication, Two Stay Two Stray, mathematics